Determinants of Farmers’ Intention of Applying New Technology in Production: The Case of Vietgap Standard Adoption in Vietnam - Tinh, Luong; Hung, Phan Tran Minh; Dzung, Doan Gia; Trinh, Vo Hoang Diem (Asian Journal of Agriculture and Rural Development, 2019)
The purpose of this paper is to identify the determinants of farmers’ intention of applying new technology with the case of VietGAP standard application in vegetable production in a developing country such as Vietnam. Using the survey data of agricultural workers in a framework of revised technology acceptance model, the analysis finds that farmers’ intention to apply or continue applying VietGAP is driven by factors such as mutual communication, awareness of benefits, environment, behavioral control, and governmental support based on authorities’ policies and risk awareness. Unlike other studies, this paper illustrates that awareness of the brand name related risk and producers’ health benefits have statistically significant impacts on farmers’ intentions.